Guideline on pregnancy and diabetes by the society of specialists in perinatology (PUDER), Turkey - ESİM BÜYÜKBAYRAK, ESRA (OrtadogÂ u Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2020)
Diabetes mellitus (DM) is the most common endocrinologic problem in pregnancy. In Turkey, the reported prevalance is between 1.9-27.9%, with an average of 7.7%. While some of these cases are pregestational diabetes (PGDM), about 90% are detected during the pregnancy for the first time and diagnosed as gestational diabetes (GDM). Diabetes in pregnancy confers serious risks regarding the fetus, newborn and the mother. Therefore, we offer GDM screening for all pregnant women preferantially between 24-28 weeks of gestation. Either one-step 75-g oral glucose tolerance test (OGTT) or two-step 50-g glucose challenge test and 100-g OGTT may be used for the screening and diagnosis. In pregnancies with high-risk for DM, screening should be performed earlier, if possible, in the first antenatal visit. When GDM is diagnosed, maternal glycemic control is tried to be achieved by diet and exercise program, and if necessary, by using insulin. The use of metformin or glyburide in pregnancy is also possible. In women with the diagnosis of DM before pregnancy, preconceptional control of plasma glucose levels is of utmost importance in order to prevent adverse pregnancy outcomes. In pregnancies with GDM regulated by diet and exercise, pregnancy follow-up may be performed as in the low risk group without any pregnancy complications. If maternal or fetal distress is not observed, delivery is planned between 39+0 -40+6 weeks. Although caesarean section is recommended when estimated fetal weight is 4500 g or more, the mode of delivery may be decided more appropriately on a case-by-case basis. Copyright © 2020 by Türkiye Klinikleri.
Keywords: Diabetes; Diabetes mellitus; Gestational; Pregnancy